Effect of Removal of Lymphoid Organ on the Acquired Immunity to Coccidiosis in Chickens - OKAMOTO, Seikan; TOJO, Hideaki (Japanese poultry science, 1970)
Studies on the role of spleen, thymus and bursa of Fabricius in the acquired immunity to E. acervulina were conducted. Male chicks used were fed a ration which contained neither antibiotics nor coccidiostats. Infection was performed by introduction of sporulated oocysts directly into the crop and the acquisition of immunity was determined by daily measurements of discharged oocysts after challenge infection. E. acervulina infection for normal birds increased thymus and spleen weights. Thymectomized birds resulted in decreased body weights following infection, while it was not observed in bursectomized birds. An increase in number of discharged oocysts was observed in thymectomized birds, compared with bursectomized, splenectomized and control birds after challenge infection. The results here suggested that thymus might play some role for the acquisition of immunity to E. acervulina.